Wzory współzależności pomiędzy jednostką a rodziną - Wrzesień, Witold; Żurek, Aldona (Wydawnictwo Naukowe UAM, 1999)
System transformation in Poland caused changes in the functioning of the family. It changed quality and character of relations between this social institution and her members. Presented article is the attempt of creation of the conceptual model essential for the further empirical research of the realisation of the patterns of interdependence between individual and the family. Pattern of interdependence is a set of norms and values responsible for the means of perception of the family by the individual and the mechanisms of interaction between the individual and the family. Patterns of interdependence determine the process of role taking and process of performing social roles within and outside the family. Apart from that they help to define individual sense of psychical comfort and quality o f life. There are several sources of interdependence between the individual and the family: a) models of practical careers existing in the society; b) individual aspirations, needs and justifications; c) quality and the character of the family life. The first part of empirical research enabled to select four basic patterns of interdependence between individual and the family: 1 ) fami ly as a manner of life; 2) family as chance and barrier of the individual activity outside the family; 3) family as a perspective of selecting choices; 4) family as a social base for the individual.
Patterns of interdependence between the individual and the family